The thinking skills of children with learning disability through creative drama and storytelling : a case study in a primary school in Jeddah - Alharthi, Arwa Mesfer (Institute of Education, International Islamic University Malaysia, 2011)
The purpose of this study is to explore whether creative drama and storytelling has an impact on enhancing the thinking skills among the Learning Disability (LD) children. The study also investigates how the creative drama and storytelling could help the LD children to learn. The study is limited to Primary School of Jeddah, Saudi Arabia. This school is known for following an inclusive outlook in their teaching and learning process. As such, data was collected from five LD children enrolled at the school. A qualitative case study design was employed over an eight-week period to explore how creative drama and storytelling will create an environment where LD children could use their thinking skills, participate in group work which enhances the LD children capability to learn. The data was collected through observation, document analysis and interviews. The analysis of the collected data revealed that during the weekly creative drama and storytelling session, the LD children had improved positively in learning and in using their thinking skills. This study sheds light on the ways that teachers can use creative drama and storytelling to create an environment that helps every LD child to learn, thereby enhancing the thinking skills of LD children. Therefore, the study recommends introducing thinking skills in the Learning Disability educational programme through using creative teaching method and adding extra classes for the students which are mainly concerned with teaching thinking skills.